Navigating the everyone-to-everyone economy - Rob van den Dam (International Telecommunications Society (ITS), 2014)
The newest digital technologies - among them social media, mobility, analytics and cloud - keep changing how people, businesses and governments interact. These digital forces enable unprecedented levels of connectedness and so the world is already investing in consumer-centricity. However, these new technologies are truly still in their infancies. The transformation that is already underway will soon intensify, resulting in a paradigm shift from customer-centricity toward an everyone-to-everyone (E2E) economy. The implication for value creation and allocation will be profound. IBM research shows that many organizations are still not ready to navigate the E2E environment. To prepare for the radical disruption ahead, companies need to act now to create experiences and business models that are orchestrated, symbiotic, contextual and cognitive.
Keywords: 330; Smarter societies; Digital; Social disruption; Big data; Transformation